Kestabilan Tegangan Menggunakan Metode Fuzzy Logic pada Sistem Distribusi 20kV - Wahyuni Martiningsih; Alvin Adam (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2023)
The stability of power system is one of high voltage issue that must be considered in the transmission and distribution system. System instability is a problem that must be handled optimally and efficiently. One way to overcome instability is by way of load shedding. This study utilizes the artificial neural network method to obtain optimal load shedding values to overcome voltage instability. Several experiments were carried out to obtain the results of the neural network architecture with the input of total generating power, total load power and several parameters of frequency rate changes. The results of network training get an MSE error value of 1.2185e-6 and network performance testing with an MSE of 0.0026672. The results of the comparison of the load shedding of the artificial neural network with an average difference of 0.036 MW and the smallest load shedding value is 0.058 MW. Can be concluded that the results of load shedding with artificial neural networks can restore the system voltage to stability.